(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
The creation of posthumous sculptural portraits poses significant challenges in the absence of morphological documentation. This study proposes a hybrid methodology that integrates generative artificial intelligence, perceptual validation, and digital modelling, focused on the production of commemorative busts with a critical approach to the creative process. AI platforms were used to generate synthetic images of the honouree’s face, which were evaluated and selected using a questionnaire administered to people who knew them during their lifetime (n = 12). The images served as the basis for the construction, reflecting on the capacity of AI to intervene in the construction of memory and representation of the body. The results show that the integration of AI not only has an impact on the sustainability of material resources, but also opens up new possibilities for questioning authorship, representative fidelity and the boundaries between technique and artistic creation. The final bust achieved a high degree of morphological and expressive recognition by the community, showing how hybrid processes can articulate collective memory, technological innovation, and aesthetic value. The methodology allows for a rigorous approach to the problems arising from the absence of data in postmortem portraits, contributing to the debate on the role of AI in...